Higher Proportion of Non-1-84 PTH Fragments in Peritoneal Dialysis Patients Compared to Hemodialysis Patients Using Solutions Containing 1.75 mmol/l Calcium - Sánchez-González, Carmen; Gonzalez-Casaus, Maria Luisa; Sellares, Víctor Lorenzo; Albalate, Marta; Torregrosa, José-Vicente; Mas, Sebastian; Ortiz, Alberto; Rodriguez, Mariano; Gonzalez-Parra, Emilio (Frontiers in Physiology, 2018)
Background: The prevalence of low- turnover bone disease (LTBD) in peritoneal dialysis (PD) patients is higher than in hemodialysis (HD) patients. LTBD patients may be at risk for vascular calcification, and cardiovascular disease. Current therapy for chronic kidney disease metabolic bone disorders (CKD-MBD) is guided by biochemical parameters, as bone biopsy is not used in routine clinical care. Methods: We assessed intact PTH (iPTH: 1-84PTH plus non-1-84PTH), 1-84PTH and the 1-84PTH/non-1-84PTH ratio in 129 hemodialysis and 73 PD prevalent patients dialyzed with solutions containing 1.75 mmol/L calcium. Results: Hemodialysis and PD patients presented similar iPTH and tCa values and prevalence of putative LTBD as defined according to KDOQI iPTH cut-off levels or 1-84 PTH levels. However, iCa accounted for a higher percentage of tCa in PD (53%) than in hemodialysis (39%) p < 0.001, and the 1-84PTH/non-1-84PTH ratio was lower in PD than in hemodialysis patients (0.44.0 ± 0.12) (vs. 0.60.3 ± 0.10.821 %), p < 0.001). The prevalence of putative LTBD when using the coexistence of 1-84PTH/non-1-84PTH ratio < 1.0 and iPTH < 420 pg/m, was higher in PD than in hemodialysis patients (73 vs. 16 % respectively, p < 0.001). In a multivariate logistic regression analysis, dialysis modality was the main determinant of the 1-84PTH/non-1-84PTH ratio. Conclusion: Solutions containing 1.75 mmol/L calciums are associated to a higher proportion of non-1-84PTH fragments in PD than in HD patients. Different analytical criteria result in widely different estimates of LTBD prevalence, thus impairing the ability of clinicians to optimize therapy for CKD-MBD.